2015
DOI: 10.3762/bjnano.6.17
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy of graphitic carbon nanomaterials doped with heteroatoms

Abstract: SummaryX-ray photoelectron spectroscopy (XPS) is one of the best tools for studying the chemical modification of surfaces, and in particular the distribution and bonding of heteroatom dopants in carbon nanomaterials such as graphene and carbon nanotubes. Although these materials have superb intrinsic properties, these often need to be modified in a controlled way for specific applications. Towards this aim, the most studied dopants are neighbors to carbon in the periodic table, nitrogen and boron, with phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
260
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(287 citation statements)
references
References 195 publications
(226 reference statements)
25
260
2
Order By: Relevance
“…Similarly, pyrrolic configuration gives rise to peaks in the range 399.8-401.2 eV, while the peak around 400.5 eV (blue colored) is associated with the graphitic configuration. The orange-colored peak at ~401.5 and 406 eV may be attributed to different nitrogenated adsorbents [20,21]. XPS results confirmed that the atomic percentages of nitrogen in S1, S2, and S3 were 0.2, 2.5, and 3.8 %, respectively [7].…”
Section: The Effects Of N Dopants In Graphene: X-ray and Raman Spectrsupporting
confidence: 60%
See 1 more Smart Citation
“…Similarly, pyrrolic configuration gives rise to peaks in the range 399.8-401.2 eV, while the peak around 400.5 eV (blue colored) is associated with the graphitic configuration. The orange-colored peak at ~401.5 and 406 eV may be attributed to different nitrogenated adsorbents [20,21]. XPS results confirmed that the atomic percentages of nitrogen in S1, S2, and S3 were 0.2, 2.5, and 3.8 %, respectively [7].…”
Section: The Effects Of N Dopants In Graphene: X-ray and Raman Spectrsupporting
confidence: 60%
“…As shown in Figure 3a, we identified XPS peaks corresponding to graphitic, pyrrolic, and pyridinic configurations [21]. For pyridinic configuration, the N1s peak positions reported in the literature are usually in the range 398.1-399.3 eV.…”
Section: The Effects Of N Dopants In Graphene: X-ray and Raman Spectrmentioning
confidence: 91%
“…[14][15][16][17] The most common forms of embedded nitrogen discussed in the literature are graphitic, pyridinic and pyrrolic nitrogen. 1,[18][19][20] Graphitic nitrogen refers to a nitrogen atom with three carbon neighbours in a hexagonal lattice, if the nitrogen is two-fold coordinated similar to that is found in pyridine, it is called pyridinic, and three-fold coordinated nitrogen in a region of defective non-aromatic lattice is associated with pyrrolic nitrogen. While the majority of reports argue that, due to their different stabilities, the concentration of these different types of nitrogen atoms in N-MWCNTs is largely controlled by the synthesis temperature 21,22 some accounts also consider the nature of the precursor to be a crucial factor.…”
Section: Introductionmentioning
confidence: 99%
“…In case of C 1s signal the following functional groups were identified [35][36][37]: graphite (sp 2 C) 284.6 ± 0.3 eV, carbon in defects (sp FWHM (full width at half maximum) was set at the same value for each component, due to the same transition, except satellite. In case of O 1s signal the following functional groups were identified [35,38]: NO 2 , C=O 531.1 ± 0.3 eV, C-O 532.8 ± 0.5 eV, and COOH 534.2 ± 0.3 eV.…”
Section: Xps Analysis X-ray Photoelectron Spectroscopy Was Performedmentioning
confidence: 99%